Analyzing the relationship between menstrual product usage, awareness of sustainable options, and health outcomes in Lucknow - Dixit, Meghna; Pandey, Abhishree; Bajpai, Maitri; Shukla, Abhinav (International Journal Of Community Medicine And Public Health, 2025)
Background: Menstrual health is a crucial aspect of women’s overall well-being, influencing personal hygiene, environmental sustainability, and social participation. In developing urban areas such as Lucknow, menstrual product usage patterns and awareness of sustainable alternatives can significantly affect both individual health and environmental outcomes. This study explores menstrual product usage among women in the Lucknow region, with a focus on sustainable well-being and environmentally responsible practices. Methods: A cross-sectional survey was conducted using a structured questionnaire to collect data from 110 women of reproductive age in the Lucknow region. The questionnaire covered menstrual product usage, awareness of sustainable alternatives, factors influencing product choices, and disposal practices. Data were analyzed to identify trends and barriers related to sustainable menstrual health practices. Results: Disposable sanitary pads emerged as the most commonly used menstrual product among participants. Awareness of sustainable alternatives- such as menstrual cups and reusable cloth pads- was low. Key barriers to adoption of sustainable products included affordability, cultural perceptions, and lack of education about their benefits. The study also found that improper disposal of menstrual products is common, contributing to environmental degradation. Conclusions: This study highlighted a significant gap in awareness and adoption of sustainable menstrual health products in Lucknow. Addressing this requires targeted interventions such as awareness campaigns, improved access to affordable sustainable products, and community-led initiatives to normalize eco-friendly menstrual practices. Promoting informed choices and proper disposal methods is essential to improving both personal and environmental well-being.